Analysis of thermal transport and fluid flow in high-temperature porous media solar thermochemical reactor. (October 2018) - Zhang, Hao; Guene Lougou, Bachirou; Pan, Ruming; Shuai, Yong; Wang, Fuqiang; Cheng, Ziming; Tan, Heping
Highlights: Deviation between LTE and LTNE increases with the increase of operating temperature. Radiation heat transfer cannot be neglected in high-temperature heat transfer processes. Porous media contributes to the uniformity of temperature and velocity distribution. Wu model of momentum source is more suitable for pressure simulation. Temperature increases with the increase of the mean cell size of porous media. Abstract: As a key technical indicator of porous media solar thermochemical reactor, thermal transport and fluid flow characteristics have significant impacts on hydrogen production efficiency. These issues could be achieved more efficiently and at a lower cost by applying computational fluid dynamics (CFD). However, the choice of different thermal transport models might cause the variation of results. In this study, the thermal transport and fluid flow characteristics in high-temperature porous media solar thermochemical reactor were investigated with different thermophysical models using FLUENT software user-defined functions (UDFs). The results indicate that the local thermal non-equilibrium model (LTNE) and radiative transfer model are proved to be indispensable for the thermal performance analysis of high working temperature thermochemical reacting system. Besides, Wu model of momentum source is more suitable for pressure simulation, while Wu model and Vafai model of heat transfer show little difference in temperature distribution.